CFTR in K562 human leukemic cells - Assef, Yanina Andrea (2003)
In this study, the expression and functional characterization of CFTR (cystic fibrosis transmembrane regulator) was determined in K562 chronic human leukemia cells. Expression of the CFTR gene product was determined by RT-PCR and confirmed by immunohistochemistry and Western blot analysis. Functional characterization of CFTR Cl channel activity was conducted with patch-clamp techniques. Forskolin, an adenylyl cyclase activator, induced an anion-selective channel with a linear current-voltage relationship and a single-channel conductance of 11 pS. This cAMP-activated channel had a Pgluconate/PCl or PF/PCl perm-selectivity ratio of 0.35 and 0.30, respectively, and was inhibited by the CFTR blocker glibenclamide and the anti-CFTR antibody MAb 13-1, when added to the cytoplasmatic side of the patch. Glibenclamide decreased the open probability increasing the frequency of open-to-closed transitions. Addition of 200 uM DIDS caused an irreversible block of the channels when added to the cytosolic side of inside-out patches. These and other observations indicate a widespread distribution of CFTR gene expression and suggest that this channel protein may function in most human cells to help maintain cellular homeostasis.